Supercapacitor energy storage method based on nano-porous copper silver and manganese dioxide composite structure
Through the composite structure of nanoporous copper-silver and manganese dioxide and the self-hydrogen oxide gas etching process, the problem of limited capacitance characteristics of MnO2 is solved, and higher specific capacity, stability and power density are achieved, and the service life of the supercapacitor is extended.
Patent Information
- Application Number
- CN202411685765.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, nanoporous metal materials fail to effectively enhance the capacitance characteristics of MnO2, and the MnO2 particles are prone to agglomeration and have poor conductivity, which limits their capacitance characteristics.
The nanoporous copper-silver and manganese dioxide composite structure is used as the electrode material. Through self-oxidation and hydrogen etching processes, the crystal lattice is widened and the oxygen vacancy is increased to promote the rapid transmission and diffusion of sodium ions/electrons.
The electrochemical reaction rate of manganese dioxide is improved, the specific capacity, stability and power density of the supercapacitor are enhanced, and the service life of the capacitor is extended.
Smart Images

Figure CN119419072A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of capacitors, and in particular relates to a supercapacitor energy storage method based on a nanoporous copper-silver and manganese dioxide composite structure. Background Art
[0002] Supercapacitors, also known as double-layer capacitors, are a new type of energy storage element between capacitors and batteries. They can be charged and discharged as quickly as capacitors, but also have the energy storage characteristics of batteries. When charging the electrode, the surface charge of the electrode in the ideal polarized electrode state will attract the opposite ions in the surrounding electrolyte solution, causing these ions to attach to the electrode surface to form a double charge layer, forming a double-layer capacitor.
[0003] At present, the main research materials for supercapacitor electrodes are carbon materials, conductive polymers and transition metal oxides. Due to the low specific capacitance of carbon materials and the poor cycle stability of conductive polymer materials, they can no longer adapt to the rapid development of supercapacitors. Therefore, people pay more attention to electrode materials based on transition metal oxides, such as MO2, NiO and Fe3O4. Among them, MnO2 has the advantages of low price, abundant reserves and high theoretical specific capacitance, making it an ideal electrode material that can best meet practical needs. However, MnO2 particles have the disadvantages of easy agglomeration and poor conductivity, which limits its capacitance characteristics. At the same time, nanoporous metal materials, as a new type of functional material with nanoscale pore size, have a continuous pore structure, a high specific surface area and good chemical stability, which makes them show unique application value in the field of new energy technology. It has been found from existing studies that using nanoporous copper as an electrode substrate material can effectively improve the capacitance characteristics of MnO2. Whether the capacitance characteristics of MnO2 can be further enhanced by refining the pore structure of nanoporous metal and improving its conductivity has become an urgent problem to be solved.
[0004] Therefore, it is necessary to propose a supercapacitor energy storage method based on a nanoporous copper-silver and manganese dioxide composite structure to solve the problem of how to use nanoporous metal to enhance the capacitance characteristics of MnO2 in the prior art.
[0005] The above information disclosed in this background technology is only used to increase the understanding of the background technology of the present invention and therefore, it may include information that does not constitute the prior art known to ordinary technicians in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a supercapacitor energy storage method based on a nanoporous copper-silver and manganese dioxide composite structure to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure includes:
[0009] Step 1: preparing nanoporous copper and silver respectively using the prepared raw materials, and compounding the nanoporous copper and silver with manganese dioxide to form a final electrode material;
[0010] Step 2: subjecting the electrode material to self-oxidation in air to obtain an oxide of the electrode material;
[0011] Step 3, subjecting the oxide of the electrode material to hydrogen etching treatment under the protection of an inert gas to obtain an etched electrode material;
[0012] Step 4: Mix the etched electrode material with a conductive agent and an adhesive to form a uniform slurry, apply the slurry evenly on the current collector, and dry the slurry in a vacuum oven to obtain an electrode sheet;
[0013] Step 5: Select two electrode sheets and a diaphragm, place them in a battery shell, inject electrolyte, and encapsulate them with a shell to make a supercapacitor;
[0014] Step 6: Test the supercapacitor using a variety of test methods to obtain test results, and optimize the structure and synthesis method of the material based on the test results.
[0015] Preferably, the aqueous solution containing copper salt and silver salt is prepared and mixed according to a set copper-silver mass ratio; a reducing agent and a surfactant are added to carry out a reduction reaction at a set temperature and time; the prepared template is immersed in the solution, and the metal ions are deposited on the template through the reduction reaction; the template is dissolved and removed using dichloromethane, washed with deionized water and dried in a vacuum oven to obtain nanoporous copper-silver.
[0016] Preferably, the prepared nanoporous copper-silver is immersed in a solution containing anhydrous ethanol; through the chemical reaction formula: 4KMnO4+3CH3CH2OH=3CH3COOK+4MnO2↓+KOH+4H2O, the MnO2 generated by the reaction forms a nucleus in the environment where the nanoporous copper-silver exists, and the reaction is allowed to stand for 8 hours; the product after the reaction is diluted with anhydrous ethanol and repeatedly washed with a centrifuge; and placed in a vacuum drying oven and dried at 60°C for 12 hours to obtain the electrode material.
[0017] Preferably, the electrode material is placed in a tubular furnace and subjected to self-oxidation treatment in air; the heating rate is set to 10°C / min, the oxidation temperature is 500°C, and the oxidation time is 1h; after cooling in the furnace, the oxide of the electrode material is obtained.
[0018] Preferably, the oxide of the electrode material is subjected to hydrogen etching treatment under the protection of an inert gas; the etching temperature is set to 200° C., the etching time is set to 10 min, and the inert gas is argon; after cooling in the furnace, the etched electrode material is obtained.
[0019] Preferably, the corresponding solvent is selected according to the solubility of the etched electrode material and the viscosity requirement of the slurry; the etched electrode material is added to the solvent in a required mass ratio and dispersed using an ultrasonic disperser; the selected conductive agent is added to the above mixture and completely dispersed by an ultrasonic disperser; during coating, the slurry is evenly distributed on the current collector using a scraper or spraying method.
[0020] Preferably, the selected diaphragm is cut according to the size of the battery shell, and dust or impurities on the surface are removed; the two electrode sheets are placed at both ends of the battery shell according to polarity according to the positive and negative polarities; the cut diaphragm is covered on the surface of the two electrode sheets without wrinkles or bubbles; the selected electrolyte is injected into the battery shell using a straw or syringe to keep the battery shell free of bubbles.
[0021] Preferably, the electrochemical behavior of the supercapacitor is tested by cyclic voltammetry; the specific capacity of the supercapacitor is measured by constant current charge and discharge test; and the internal impedance characteristics of the supercapacitor are analyzed by electrochemical impedance spectroscopy test.
[0022] Preferably, the specific capacity, stability and power density of the supercapacitor are further improved by adjusting the porosity of the nanoporous copper-silver, the morphology and deposition amount of manganese dioxide; and the electrochemical properties of the electrode material are further improved by doping with different elements or using different synthesis methods.
[0023] Preferably, the method also applies the optimized supercapacitor to actual energy storage devices to conduct a comprehensive evaluation of energy density, power density and cycle life. If the performance is excellent, it can be further used in high-performance energy storage devices such as electric vehicles and portable electronic devices.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses nanoporous copper-silver composites with manganese dioxide as electrode materials to provide a larger specific surface area, increase electronic conductivity, and improve the contact effect between the electrolyte and the electrode; combined with self-oxidation and hydrogen etching processes, the lattice is widened and oxygen vacancies are increased to promote rapid transmission and diffusion of sodium ions / electrons, thereby enhancing the electrochemical reaction rate of manganese dioxide.
[0026] The present invention utilizes nanoporous copper and silver as a conductive skeleton, which can effectively alleviate the volume expansion problem of manganese dioxide, improve the structural stability of manganese dioxide, and extend the service life of the capacitor; due to its good conductivity and structural design, nanoporous copper and silver enhanced manganese dioxide can support higher charge and discharge rates, thereby improving the performance of supercapacitors in fast charging and high-power applications.
[0027] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a flow chart of the supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1:
[0031] See also Figure 1 As shown, a supercapacitor energy storage method based on a nanoporous copper-silver and manganese dioxide composite structure includes:
[0032] Step 1: using the prepared raw materials to prepare nanoporous copper and silver respectively, and compounding the nanoporous copper and silver with manganese dioxide to form a final electrode material;
[0033] Step 2: subjecting the electrode material to self-oxidation in air to obtain an oxide of the electrode material;
[0034] Step 3, subjecting the oxide of the electrode material to hydrogen etching treatment under the protection of an inert gas to obtain an etched electrode material;
[0035] Step 4: Mix the etched electrode material with a conductive agent and an adhesive to form a uniform slurry, apply the slurry evenly on the current collector, and dry the slurry in a vacuum oven to obtain an electrode sheet;
[0036] Step 5: Select two electrode sheets and a diaphragm, place them in a battery shell, inject electrolyte, and encapsulate them with a shell to make a supercapacitor;
[0037] Step 6: Test the supercapacitor using a variety of test methods to obtain test results, and optimize the material structure and synthesis method based on the test results.
[0038] An aqueous solution containing copper salt and silver salt is prepared and mixed according to a set copper-silver mass ratio; a reducing agent and a surfactant are added to carry out a reduction reaction at a set temperature and time; the prepared template is immersed in the solution, and metal ions are deposited on the template through a reduction reaction; dichloromethane is used to dissolve and remove the template to obtain nanoporous copper-silver.
[0039] The prepared nanoporous copper-silver was immersed in a solution containing anhydrous ethanol; the MnO2 generated by the reaction was made to form a nucleus in the environment where the nanoporous copper-silver existed through the chemical reaction formula: 4KMnO4+3CH3CH2OH=3CH3COOK+4MnO2↓+KOH+4H2O, and the amount of KMnO4 solution added was controlled by using the equivalent relationship in the reaction formula so that the molar ratio of the nanoporous copper-silver to manganese dioxide was 1:3, and the reaction was allowed to stand for 8 hours; the product after the reaction was diluted with anhydrous ethanol and repeatedly washed with a centrifuge; it was placed in a vacuum drying oven and dried at 60°C for 12 hours to obtain an electrode material.
[0040] The electrode material is placed in a tube furnace and subjected to self-oxidation treatment in air; the heating rate is set to 10°C / min, the oxidation temperature is set to 500°C, and the oxidation time is set to 1h; after cooling in the furnace, the oxide of the electrode material is obtained.
[0041] The oxide of the electrode material is subjected to hydrogen etching treatment under the protection of an inert gas; the etching temperature is set to 200° C., the etching time is set to 10 min, and the inert gas is argon; after cooling with the furnace, the etched electrode material is obtained.
[0042] According to the solubility of the etched electrode material and the viscosity requirements of the slurry, the corresponding solvent is selected; the etched electrode material is added to the solvent in the required mass ratio and dispersed using an ultrasonic disperser; the selected conductive agent is added to the above mixture and completely dispersed using an ultrasonic disperser; during coating, the slurry is evenly distributed on the current collector using a scraper or spraying method.
[0043] Test Example 1: Using nanoporous copper and manganese dioxide composite electrode sheets and pure manganese dioxide and the electrode sheets prepared above, CV (cyclic voltammetry) cycle tests were carried out under the same conditions, and the test scan rate was 10mV / s. The specific capacitance values of pure manganese dioxide and nanoporous copper and manganese dioxide composite electrode sheets were 154 and 231F / g, respectively, while the specific capacitance value of the electrode sheet prepared above reached 300F / g, which is higher than the specific capacitance value of pure manganese dioxide and nanoporous copper and manganese dioxide composite electrode sheets. It can be seen that the electrode sheet prepared above has obvious advantages over nanoporous copper. In addition, the cycle stability test of the electrode sheet prepared above was carried out at a scan speed of 50mV / s and 1mol / LNa2SO4 electrolyte. After 3000 cycles, the specific capacitance value of the electrode sheet prepared above was 87% of the initial value, indicating that the electrode sheet prepared above has good cycle stability.
[0044] Embodiment 2:
[0045] See also Figure 1 As shown, this embodiment is basically the same as the above embodiment, except that the selected diaphragm is cut according to the size of the battery shell, and dust or impurities on the surface are removed; the two electrode sheets are placed at both ends of the battery shell according to the polarity according to the positive and negative polarities; the cut diaphragm is covered on the surface of the two electrode sheets without wrinkles or bubbles; a straw or syringe is used to inject the selected electrolyte into the battery shell to keep the battery shell free of bubbles.
[0046] The electrochemical behavior of supercapacitors was tested using cyclic voltammetry. The specific capacity of supercapacitors was measured using constant current charge and discharge tests. The internal impedance characteristics of supercapacitors were analyzed using electrochemical impedance spectroscopy tests.
[0047] Test Example 2: The electrode material was analyzed using a Bruker D8 X-ray difractometer. The electrode material was observed for microscopic morphology using a Hitachi S-4800 field emission scanning electron microscope, and the above electrode material was subjected to energy spectrum analysis to detect the component elements and content in the electrode material. The prepared electrode was subjected to cyclic voltammetric characteristics and constant current charge and discharge tests using a Shanghai Chenhua chi660e electrochemical workstation. The electrochemical test used a three-electrode system, namely a working electrode, a reference electrode, and an auxiliary electrode, wherein the working electrode was the electrode to be tested, the reference electrode was Ag / AgCI, and the auxiliary electrode was a platinum electrode. The test voltage range was -0.2 to 0.8 V, and the test electrolyte was 0.5 mol / L Na2SO4 and 1 mol / L Na2SO4 solutions.
[0048] By adjusting the porosity of nanoporous copper and silver, the morphology and deposition amount of manganese dioxide, the specific capacity, stability and power density of the supercapacitor can be further improved; the electrochemical properties of the electrode material can be further improved by doping different elements or using different synthesis methods.
[0049] This method will also apply the optimized supercapacitors to actual energy storage devices to conduct a comprehensive evaluation of energy density, power density and cycle life. If the performance is excellent, it can be further used in high-performance energy storage devices such as electric vehicles and portable electronic devices.
[0050] As can be seen from the above, the present invention uses nanoporous copper-silver composites with manganese dioxide as electrode materials to provide a larger specific surface area, increase electronic conductivity, and improve the contact effect between the electrolyte and the electrode; combined with self-oxidation and hydrogen etching processes, the lattice is widened and oxygen vacancies are increased to promote rapid transmission and diffusion of sodium ions / electrons, thereby enhancing the electrochemical reaction rate of manganese dioxide.
[0051] The present invention utilizes nanoporous copper and silver as a conductive skeleton, which can effectively alleviate the volume expansion problem of manganese dioxide, improve the structural stability of manganese dioxide, and extend the service life of the capacitor; due to its good conductivity and structural design, nanoporous copper and silver enhanced manganese dioxide can support higher charge and discharge rates, thereby improving the performance of supercapacitors in fast charging and high-power applications.
[0052] Embodiment 3:
[0053] The embodiment of the present invention further provides a computer-readable storage medium, on which a computer program is stored, and when the computer program is executed by a processor, each process of the above energy storage method embodiment is implemented, and the same technical effect can be achieved. To avoid repetition, it is not repeated here. Among them, the computer-readable storage medium, such as read-only memory (Read-Only Memory, referred to as ROM), random access memory (Random Access Memory, referred to as RAM), a disk or an optical disk, etc.
[0054] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.
[0055] The present invention is described with reference to flowcharts and / or block diagrams of methods, devices (systems) and computer program products according to embodiments of the present invention. It should be understood that each process and / or block in the flowchart and / or block diagram, as well as the combination of processes and / or blocks in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor or other programmable data processing device to generate a program, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A way to specify functions in one or more boxes.
[0056] In the drawings of the embodiments disclosed in the present invention, only the structures involved in the embodiments disclosed in the present invention are involved, and other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of the present invention can be combined with each other.
[0057] The flowcharts shown in the accompanying drawings are only examples and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps may also be decomposed, combined or partially merged, so the actual execution order may change according to actual conditions.
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A supercapacitor energy storage method based on a nanoporous copper-silver and manganese dioxide composite structure, characterized in that: The following steps are involved: Step 1: preparing nanoporous copper and silver respectively using the prepared raw materials, and compounding the nanoporous copper and silver with manganese dioxide to form a final electrode material; Step 2: subjecting the electrode material to self-oxidation in air to obtain an oxide of the electrode material; Step 3, subjecting the oxide of the electrode material to hydrogen etching treatment under the protection of an inert gas to obtain an etched electrode material; Step 4: Mix the etched electrode material with a conductive agent and an adhesive to form a uniform slurry, apply the slurry evenly on the current collector, and dry the slurry in a vacuum oven to obtain an electrode sheet; Step 5: Select two electrode sheets and a diaphragm, place them in a battery shell, inject electrolyte, and encapsulate them with a shell to make a supercapacitor; Step 6: Test the supercapacitor using a variety of test methods to obtain test results, and optimize the structure and synthesis method of the material based on the test results.
2. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 1 is characterized in that: The method of using the prepared raw materials to prepare nanoporous copper and silver respectively comprises: preparing an aqueous solution containing a copper salt and a silver salt, and mixing them according to a set copper-silver mass ratio; Add reducing agent and surfactant, and carry out reduction reaction at set temperature and time; The prepared template is immersed in the solution, and the metal ions are deposited on the template through a reduction reaction; The template was dissolved and removed using dichloromethane to obtain nanoporous copper-silver.
3. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 2 is characterized in that: The nanoporous copper-silver compound is combined with manganese dioxide to form a final electrode material, comprising: Immersing the prepared nanoporous copper-silver in a solution containing anhydrous ethanol; Through the chemical reaction formula: 4KMnO4+3CH3CH2OH=3CH3COOK+4MnO2↓+KOH+4H2O, the MnO2 generated by the reaction forms a nucleus in the environment where the nanoporous copper and silver exist, and the reaction is allowed to stand for 8 hours; The product after the reaction was diluted with anhydrous ethanol and washed repeatedly with a centrifuge; The mixture was placed in a vacuum drying oven and dried at 60° C. for 12 h to obtain the electrode material.
4. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 3 is characterized in that: The step of subjecting the electrode material to self-oxidation in air to obtain an oxide of the electrode material comprises: placing the electrode material in a tube furnace and performing autoxidation treatment in air; Set the heating rate to 10°C / min, the oxidation temperature to 500°C, and the oxidation time to 1h; After cooling in the furnace, the oxide of the electrode material is obtained.
5. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 4 is characterized in that: The step of subjecting the oxide of the electrode material to hydrogen etching under the protection of an inert gas to obtain the etched electrode material comprises: The oxide of the electrode material is subjected to hydrogen etching treatment under the protection of an inert gas; Set the etching temperature to 200°C, the etching time to 10 min, and the inert gas to argon; After cooling in the furnace, the etched electrode material is obtained.
6. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 5, characterized in that: The etched electrode material is mixed with a conductive agent and an adhesive to form a uniform slurry and is evenly coated on the current collector, comprising: Select the corresponding solvent according to the solubility of the electrode material after etching and the viscosity requirements of the slurry; The etched electrode material is added into a solvent according to a required mass ratio, and dispersed using an ultrasonic disperser; Adding the selected conductive agent to the above mixture and dispersing it completely by using an ultrasonic disperser; During coating, a scraper or spray coating method is used to evenly distribute the slurry on the current collector.
7. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 6 is characterized in that: The method comprises: selecting two electrode sheets and a separator, placing them in a battery shell, and injecting an electrolyte, comprising: Cut the selected diaphragm according to the size of the battery shell and remove dust or impurities on the surface; Placing the two electrode sheets at both ends of the battery case according to the positive and negative polarities; Covering the cut diaphragm on the surfaces of the two electrode sheets without wrinkles or bubbles; Use a pipette or syringe to inject the selected electrolyte into the battery case, keeping no bubbles in the battery case.
8. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 7, characterized in that: The supercapacitor is tested by a variety of testing methods, including: The electrochemical behavior of the supercapacitor was tested using cyclic voltammetry; Measuring the specific capacity of the supercapacitor by constant current charge and discharge test; The internal impedance characteristics of the supercapacitor were analyzed by electrochemical impedance spectroscopy.
9. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 8, characterized in that: The method of optimizing the structure and synthesis of the material according to the test results includes: By adjusting the porosity of the nanoporous copper-silver, the morphology and deposition amount of manganese dioxide, the specific capacity, stability and power density of the supercapacitor are further improved; The electrochemical performance of the electrode material can be further improved by doping with different elements or using different synthesis methods.
10. The supercapacitor energy storage method based on the nanoporous copper-silver and manganese dioxide composite structure according to claim 9, characterized in that: The method also applies the optimized supercapacitors to actual energy storage devices to conduct a comprehensive evaluation of energy density, power density and cycle life.
Citation Information
Patent Citations
Nano-porous copper silver supported manganese dioxide electrode slice and preparation method therefor
CN104867681A
Flexible nano-porous metal oxide negative electrode used for secondary battery and manufacturing method thereof
CN110635103A
Quinary high-entropy alloy oxide negative electrode material and preparation method and application thereof
CN113258050A
Shape controllable, transferable ordered through-hole thin film material and preparation method thereof
CN1704149A